PEMBERDAYAAN MASYARAKAT DALAM PENGELOLAAN OBAT TRADISONAL - Bingar Hernowo (LPPM STIKES Madani, 2022)
Until now, people think that consuming and managing traditional medicine does not require regulations like chemical drugs. This is due to the lack of information and education about the management of traditional medicines in the community. The same thing also happened to the people of Nyamplung Hamlet, Srimulyo Village, Bantul Regency. Based on the results of the conversation between the servants and several people, it was found that traditional medicine was their main choice in sick conditions, especially in the pandemic era. The classic problem is that they also don't know that traditional medicine requires management procedures so that the results can be maximized and not dangerous. In addition to the factor of not wanting to read, so far there has been no education to them related to the management of both chemical and traditional medicines. The community service program in Nyamplung Hamlet, Srimulyo Village, Bantul Regency has been going well and according to plan. The response of the community as participants seemed enthusiastic and could follow well. The results of the activity evaluation show that the community is able to understand the material well and is committed to applying it in their daily lives